Bone Cells Survival After Liquid Nitrogen Freezing: Does Time Play a Role? - Irsan, Istan; Isma, Satria; Vivayuna, Inggra; Norahmawati, Eviana; Sukmajaya, William; Pandiangan, Ray; Abduh, Muhammad (Problems of Cryobiology and Cryomedicine, 2021)
Probl Cryobiol Cryomed 2021; 31(1): 089–094